Quality-labeled vegetable consumption in Malaysia: factors affecting attitude and purchase intent - Rezai, Golnaz; Shamsudin, Mad Nasir; Mohamed, Zainal Abidin; Chong, Sook Ann (Routledge, 2014)
The rising rate of foodborne diseases has caused not just consumers but also food producers to become increasingly concerned about food safety. As a result, the government of Malaysia, together with relevant bodies, have introduced quality-assurance agencies to certify food products that are produced, processed, and handled with methods that are acknowledged by the certification agencies as clean and safe for consumption. This study aims to identify the factors influencing consumer purchasing behavior toward quality-labeled vegetables. A survey was conducted using a self-administered questionnaire and distributed randomly to consumers in public places in the Klang Valley. Four hundred and sixteen respondents were approached. The results indicate that most of the respondents are aware of food quality labels. Using factor analysis, four latent factors that influence consumer attitude toward quality-labeled vegetables were identified, and the importance of quality attributes (sensory, health, safety, and social attributes) in shaping those attitudes was also shown.